THE CORELATION OF PARENTS USING THERAPEUTIC COMMUNICATION WITH THE LENGTH OF TIME USING GADGETS IN A DAY 24 HOURS IN EARLY CHILHOOD (3-8 YEARS OLD) IN CIANTRA VILLAGE PEACOCK ALLEY IX 2022 - Utami, Sri; Nurti Y.K. Gea; Baltasar S. S. Dedu (Soscience: Jurnal Ilmu Sosial Science, 2023)
The flow of globalization that cannot be separated from human life at this time which greatly affects daily life, one of which is communication. Communication is the provision of infomation, news, or interaction carried out by two or more people in the hope that there will be feedback given after listening to the information. The communication tool that can be used in this case is using therapeutic communication. Therapeutic communication can not only be done by nurses but parents to see  the lenght of time using gadgets that occur in children. Gadgets is a telecomunications medium taht has ad small form that is easy to carry and is widely used today. This is clear evidence of the development of science and tacholog (science technology) at this time, gadgets are able to influence humans both in terms of mindset and behavior. The study aims to determine”The Corelation Of Parents Using Therapeutic Communication With The Length Of Time Using Gadgets In A Day 24 Hours In Early Chilhood (3-8 Years Old) In Ciantra Village Peacock Alley IX 2022”. The type of quantitative research with cross sectional method. The population is parents who have an early age of 3-8 years with a total of 34 respondents. Sampling techique using total sampling. The result obtained with a significannt level of 95% of a value of 5% (0,05) obtained p value (0,005) < value (0,05) so taht it can be concluded from these results that H0 is rejected, meaning that there is a The Corelation Of Parents Using Therapeutic Communication With The Length Of Time Using Gadgets In A Day 24 Hours In Early Chilhood (3-8 Years Old) In Ciantra Village Peacock Alley IX 2022. There is a The Corelation Of Parents Using Therapeutic Communication With The Length Of Time Using Gadgets In A Day 24 Hours In Early Chilhood (3-8 Years Old) In Ciantra Village Peacock Alley IX 2022.